Job Burnout and its Relationship to the Future Orientation of Country Employees - Karim Rashk Sajet; Mahdi Saleh Blasm; Ali Odeh Muhammad; Abdul Qadir Hussein Hamad (Zanco Journal of Human Sciences, 2025)
The research aims to know; Job burnout among country employees. The future orientation of country employees. The correlation between job burnout and future orientation among country employees. In order to achieve the research objectives, the researchers adopted the Maslach and Jackson scale (Maslach, Jackson, 1981), which was codified by (Abu Masoud, 2010) as a tool for measuring job burnout. The scale consists of (16) items distributed over three areas, namely (emotional exhaustion), (Dampening of feelings), (decrease in personal achievement), and the future orientation scale was built according to Seginer’s theory (Seginer, 2009). The scale consists of (28) items distributed over three areas (future perceptions, planning for the future, and self-efficacy. After applying the two tools to a sample of 400 employees from departments who were selected by a stratified random method with proportional selection, the researchers extracted a set of psychometric properties for both measures, including discrimination, validity, and reliability. The search results indicated the percentage of individuals who have a high level of job burnout (18.25%) out of the total research sample is higher than the percentage of those who have a low level (16% The percentage of individuals who have a low level of future orientation (19.5%) out of the total research sample is higher than the percentage of those who have a high level 18% The relationship between the two variables is a statistically significant inverse relationship, meaning that the higher the individual’s job burnout, the lower his orientation toward the future Based on these results, the researchers presented a set of recommendations and suggestions for subsequent research